The Effect of Training and Work Equipment on Improving Employee Performance at PT. Hasema Philip - Amin Toto Raharjo; Yuni Pratikno; Jamal Hanaffy (Dinasti Publisher, 2026)
The purpose of this research is to answer the problem formulation that has been determined, namely: To analyze the effect of training on improving employee performance, To analyze the effect of work equipment on improving employee performance. To analyze the effect of training and work equipment simultaneously on improving employee performance at PT. Hasema Philip. Training (X1) has an effect on employee performance (Y) . The calculated t value is 5.603, which is greater than the t table of 1.986 at a significance level of 5%. Work Equipment (X2) has an effect on employee performance (Y ). The results of the t test show that the calculated t value is 11.497, which is greater than the t table of 1.986 . The F test shows that the calculated F value is 190.541, which is greater than the F table. 2.70 , significance of 0.000 < 0.05. R value Square of 0.811 , that 81.1% of employee performance can be explained by Training and Work Equipment , while the remaining 18.9% is influenced by other factors not examined in this study